Pengaruh Model Pembelajaran Role Playing Terhadap Minat Belajar Pak Siswa Di Kelas VIII SMP Negeri 2 Siborongborong Tahun Pembelajaran 2022/2023 - Aritha Raja Guk Guk; Tianggur Napitupulu; Dame Taruli (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
The aim of this research is to find out whether there is an influence of the role playing learning model on students' interest in learning PAK in class VIII of SMP Negeri 2 Siborongborong for the 2022/2023 academic year. The research method used is a quantitative method of inferential statistics. The population was all 221 students of class VIII of SMP Negeri 2 Siborongborong who were Christians and a sample of 42 people was determined using random sampling techniques. Data was collected using a positive closed questionnaire with 36 items, namely 20 items for variable : 1) Test the analysis requirements: a) positive relationship test obtained rxy = 0.407 > rtable(=0.05,n=42) = 0.304. b) Testing a significant relationship obtained tcount= 4.815 > ttable(=0.05,dk=n-2=40)= 2.021. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y ̂="18.38"+0.51X. b) Regression coefficient of determination test (r2) = 16.5%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=19, dk denominator=n-2=42-2=40) namely 7.92 > 1.51. Thus Ha is accepted and H0 is rejected.